Optical laminate and display system

JP2025042572APending Publication Date: 2025-03-27NITTO DENKO CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024022095
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-14
Filing Date
2024-02-16
Publication Date
2025-03-27

Smart Images

  • Figure 2025042572000001_ABST
    Figure 2025042572000001_ABST
Patent Text Reader

Abstract

To provide an optical laminate which may contribute to improvement in display characteristics of VR goggles.SOLUTION: A display system according to an embodiment of the present invention comprises: a display element having a display surface for emitting light representing an image forward through a polarizing member; a reflector unit with a reflective polarizing member disposed in front of the display element and designed to reflect the light emitted from the display element; a first lens unit disposed on an optical path between the display element and the reflector unit, a half-mirror located between the display element and the first lens unit and designed to transmit the light emitted form the display element and reflect the light reflected by the reflector unit toward the reflector unit; a first retardation member located on an optical path between the display element and the half-mirror; and a second retardation member located on an optical path between the half-mirror and the reflector unit. The polarizing member and the first retardation member constitute an optical laminate comprising the polarizing member, a layer serving as a λ / 2 plate, and a layer serving as a λ / 4 plate in the described order.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an optical stack and a display system. [Background technology]

[0002] Image display devices, such as liquid crystal display devices and electroluminescence (EL) display devices (e.g., organic EL display devices), are rapidly becoming widespread. In image display devices, optical members such as polarizing members and phase difference members are generally used to realize image display and to improve the performance of the image display (see, for example, Patent Document 1).

[0003] In recent years, new applications of image display devices have been developed. For example, goggles with displays (VR goggles) for realizing Virtual Reality (VR) have started to be commercialized. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2021-103286 A Summary of the Invention [Problem to be solved by the invention]

[0005] In view of the above, a primary object of the present invention is to provide an optical laminate that can contribute to improving the display characteristics of VR goggles. [Means for solving the problem]

[0006] 1. A display system according to an embodiment of the present invention is a display system that displays an image to a user, comprising: a display element having a display surface that emits light representing an image forward via a polarizing member; a reflecting section that is arranged in front of the display element and includes a reflective polarizing member and reflects the light emitted from the display element; a first lens section that is arranged on an optical path between the display element and the reflecting section; a half mirror that is arranged between the display element and the first lens section and transmits the light emitted from the display element and reflects the light reflected by the reflecting section towards the reflecting section; a first phase difference member that is arranged on the optical path between the display element and the half mirror; and a second phase difference member that is arranged on the optical path between the half mirror and the reflecting section, wherein the polarizing member and the first phase difference member constitute an optical stack, and the optical stack comprises, in this order, a polarizing member, a layer that functions as a λ / 2 plate, and a layer that functions as a λ / 4 plate. 2. An optical laminate according to an embodiment of the present invention includes a polarizing member, a layer functioning as a λ / 2 plate, and a layer functioning as a λ / 4 plate, in that order, and is used in the display system described in 1 above. 3. In the optical laminate described in 2 above, the layer functioning as a λ / 2 plate may have an in-plane retardation Re(550) of 230 nm to 330 nm. 4. In the optical laminate according to 2 or 3 above, the layer functioning as a λ / 4 plate may have an in-plane retardation Re(550) of 100 nm to 200 nm. 5. In the optical laminate according to any one of 2 to 4 above, the angle between the slow axis of the layer functioning as a λ / 2 plate and the absorption axis of the polarizing member may be 5° to 35°. 6. In the optical laminate according to any one of 2 to 5 above, the angle between the slow axis of the layer functioning as the λ / 4 plate and the absorption axis of the polarizing member may be 55° to 85°. 7. In the optical laminate according to any one of 2 to 6 above, the layer functioning as a λ / 2 plate may exhibit inverse dispersion wavelength characteristics. 8. In the optical laminate according to any one of 2 to 7 above, the layer functioning as a λ / 4 plate may exhibit inverse dispersion wavelength characteristics. 9. The optical laminate described in any one of 2 to 8 above may further include a member whose refractive index characteristics exhibit the relationship nz>nx=ny, and the member whose refractive index characteristics exhibit the relationship nz>nx=ny may be arranged on the opposite side of the layer functioning as the λ / 4 plate to the layer functioning as the λ / 2 plate. 10. The optical laminate according to any one of 2 to 9 above, further comprising an anti-reflection protective member, the anti-reflection protective member being disposed on the outermost side opposite to the polarizing member. 11. The optical laminate according to any one of 2 to 10 above may have a depolarization index (DI) of transmitted light having a wavelength of 550 nm measured at a polar angle of 0° (1-DI) of 99.5% or more. 12. The optical laminate according to any one of 2 to 11 above may have a depolarization index (DI) of transmitted light having a wavelength of 550 nm, measured at a polar angle of 30° and an azimuth angle of 0° to 360°, subtracted from 1 (1-DI) to be 99.4% or more. 13. The optical laminate described in any one of 2 to 12 above may be used as the first phase difference member in a display method having the steps of: passing light representing an image emitted via a polarizing member through a first phase difference member; passing the light that has passed through the first phase difference member through a half mirror and a first lens unit; passing the light that has passed through the half mirror and the first lens unit through a second phase difference member; reflecting the light that has passed through the second phase difference member toward the half mirror with a reflective polarizing member; and making the light reflected by the reflective polarizing member and the half mirror transmittance through the reflective polarizing member by the second phase difference member. Effect of the Invention

[0007] According to the present invention, it is possible to provide an optical laminate that can contribute to improving the display characteristics of VR goggles. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1 is a schematic diagram showing a general configuration of a display system according to an embodiment of the present invention. [Diagram 2] 1 is a schematic cross-sectional view of an optical laminate according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, the embodiments of the present invention will be described with reference to the drawings, but the present invention is not limited to these embodiments. In order to clarify the description, the drawings may be schematic in terms of the width, thickness, shape, etc. of each part compared to the embodiment, but they are merely examples and do not limit the interpretation of the present invention. In addition, in the drawings, the same or equivalent elements are given the same reference numerals, and duplicate descriptions may be omitted.

[0010] (Definition of terms and symbols) The definitions of terms and symbols used in this specification are as follows. (1) Refractive index (nx, ny, nz) "nx" is the refractive index in the direction in which the in-plane refractive index is maximum (i.e., the slow axis direction), "ny" is the refractive index in the direction perpendicular to the slow axis in the plane (i.e., the fast axis direction), and "nz" is the refractive index in the thickness direction. (2) In-plane phase difference (Re) "Re(λ)" is the in-plane retardation measured with light of wavelength λ nm at 23° C. For example, "Re(550)" is the in-plane retardation measured with light of wavelength 550 nm at 23° C. Re(λ) is calculated by the formula: Re(λ)=(nx-ny)×d, where d(nm) is the thickness of the layer (film). (3) Retardation in the thickness direction (Rth) "Rth(λ)" is the retardation in the thickness direction measured with light of wavelength λ nm at 23° C. For example, "Rth(550)" is the retardation in the thickness direction measured with light of wavelength 550 nm at 23° C. Rth(λ) is calculated by the formula: Rth(λ)=(nx-nz)×d, where d(nm) is the thickness of the layer (film). (4) Nz coefficient The Nz coefficient is calculated by Nz=Rth / Re. (5)Angle When an angle is mentioned in this specification, the angle includes both clockwise and counterclockwise angles with respect to a reference direction unless otherwise specified. Thus, for example, "45°" means ±45°. In this specification, "substantially parallel" includes a range of 0°±10°, preferably within a range of 0°±5°, more preferably within a range of 0°±3°, and even more preferably within a range of 0°±1°. "Substantially perpendicular" includes a range of 90°±10°, preferably within a range of 90°±5°, more preferably within a range of 90°±3°, and even more preferably within a range of 90°±1°.

[0011] A. Display System FIG. 1 is a schematic diagram showing a schematic configuration of a display system according to one embodiment of the present invention. In FIG. 1, the arrangement and shape of each component of a display system 2 are illustrated. The display system 2 includes a display element 12, a reflecting section 14 including a reflective polarizing member, a first lens section 16, a half mirror 18, a first phase difference member 20, a second phase difference member 22, and a second lens section 24. The reflecting section 14 is disposed in front of the display surface 12a side of the display element 12, and can reflect light emitted from the display element 12. The first lens section 16 is disposed on the optical path between the display element 12 and the reflecting section 14, and the half mirror 18 is disposed between the display element 12 and the first lens section 16. The first phase difference member 20 is disposed on the optical path between the display element 12 and the half mirror 18, and the second phase difference member 22 is disposed on the optical path between the half mirror 18 and the reflecting section 14. The components arranged in front of the half mirror (in the illustrated example, the half mirror 18, the first lens portion 16, the second phase difference member 22, the reflecting portion 14 and the second lens portion 24) may be collectively referred to as the lens portion (lens portion 4).

[0012] The display element 12 is, for example, a liquid crystal display or an organic EL display, and has a display surface 12a for displaying an image. The light emitted from the display surface 12a passes through, for example, a polarizing member (typically, a polarizing film) that may be included in the display element 12, and is converted into a first linearly polarized light.

[0013] The first phase difference member 20 can convert the first linearly polarized light incident on the first phase difference member 20 into the first circularly polarized light. The first phase difference member 20 can be provided integrally with the display element 12, as shown in FIG. 1. Specifically, a polarizing member that can be included in the display element 12 and the first phase difference member 20 can be provided integrally to configure an optical laminate 200 described later. In other words, a laminate including a layer 20a that functions as a λ / 2 plate and a layer 20b that functions as a λ / 4 plate in the optical laminate 200 described later can be the first phase difference member 20 in the display system 2.

[0014] The half mirror 18 transmits the light emitted from the display element 12 and reflects the light reflected by the reflecting portion 14 toward the reflecting portion 14. The half mirror 18 is provided integrally with the first lens portion 16.

[0015] The second phase difference member 22 is a λ / 4 member that can transmit the light reflected by the reflecting section 14 and the half mirror 18 through the reflecting section 14 including a reflective polarizing member (hereinafter, the second phase difference member may be referred to as a second λ / 4 member). The second phase difference member 22 may be provided integrally with the first lens section 16.

[0016] The first circularly polarized light output from the phase difference member (first phase difference member) 20 passes through the half mirror 18 and the first lens unit 16, and is converted into the second linearly polarized light by the second λ / 4 member 22. The second linearly polarized light output from the second λ / 4 member 22 is reflected toward the half mirror 18 without passing through the reflective polarizing member included in the reflecting unit 14. At this time, the polarization direction of the second linearly polarized light that is incident on the reflective polarizing member included in the reflecting unit 14 is the same as the reflection axis of the reflective polarizing member. Therefore, the second linearly polarized light that is incident on the reflecting unit 14 is reflected by the reflective polarizing member.

[0017] The second linearly polarized light reflected by the reflecting unit 14 is converted into the second circularly polarized light by the second λ / 4 member 22, and the second circularly polarized light emitted from the second λ / 4 member 22 passes through the first lens unit 16 and is reflected by the half mirror 18. The circularly polarized light reflected by the half mirror 18 passes through the first lens unit 16 and is converted into the third linearly polarized light by the second λ / 4 member 22. The third linearly polarized light passes through the reflective polarizing member included in the reflecting unit 14. At this time, the polarization direction of the third linearly polarized light incident on the reflective polarizing member included in the reflecting unit 14 is the same as the transmission axis of the reflective polarizing member. Therefore, the third linearly polarized light incident on the reflecting unit 14 passes through the reflective polarizing member.

[0018] The light transmitted through the reflecting portion 14 passes through the second lens portion 24 and enters the user's eye 26.

[0019] For example, the absorption axis of the polarizing member included in the display element 12 and the reflection axis of the reflective polarizing member included in the reflecting section 14 may be arranged substantially parallel to each other or substantially perpendicular to each other. The angle between the absorption axis of the polarizing member included in the display element 12 and the slow axis of the first phase difference member 20 and the in-plane phase difference of the first phase difference member 20 are set so as to convert the first linearly polarized light into the first circularly polarized light. The above angle and in-plane phase difference will be described in detail in Section B. The angle between the absorption axis of the polarizing member included in the display element 12 and the slow axis of the second phase difference member 22 is, for example, 40° to 50°, may be 42° to 48°, or may be about 45°.

[0020] The in-plane retardation Re(550) of the second retardation member 22 is, for example, 100 nm to 190 nm, may be 110 nm to 180 nm, may be 130 nm to 160 nm, or may be 135 nm to 155 nm.

[0021] The second retardation member 22 preferably exhibits an inverse dispersion wavelength characteristic in which the retardation value increases according to the wavelength of the measurement light. Re(450) / Re(550) of the second retardation member 22 is, for example, less than 1, may be 0.95 or less, may further be less than 0.90, and may further be 0.85 or less. Re(450) / Re(550) of the second retardation member 22 is, for example, 0.75 or more.

[0022] In one embodiment, the second retardation member 22 satisfies all of Re(400) / Re(550) < 0.85, Re(650) / Re(550) > 1.03, and Re(750) / Re(550) > 1.05. The second retardation member 22 preferably satisfies at least one selected from 0.65 < Re(400) / Re(550) < 0.80 (preferably, 0.7 < Re(400) / Re(550) < 0.75), 1.0 < Re(650) / Re(550) < 1.25 (preferably, 1.05 < Re(650) / Re(550) < 1.20), and 1.05 < Re(750) / Re(550) < 1.40 (preferably, 1.08 < Re(750) / Re(550) < 1.36), more preferably satisfies at least two, and even more preferably satisfies all of them.

[0023] The second retardation member 22 preferably exhibits a refractive index characteristic showing a relationship of nx > ny ≧ nz. Here, “ny = nz” includes not only the case where ny and nz are exactly equal but also the case where they are substantially equal. Therefore, within a range not impairing the effects of the present invention, ny < nz may occur. The Nz coefficient of the second retardation member 22 is preferably 0.9 to 3, more preferably 0.9 to 2.5, even more preferably 0.9 to 1.5, and particularly preferably 0.9 to 1.3.

[0024] The surface smoothness of the second phase difference member 22 is, for example, 0.50 arcmin or less, preferably 0.40 arcmin or less, more preferably 0.30 arcmin or less, and further preferably 0.20 arcmin or less. When the second phase difference member 22 satisfies such surface smoothness, a display system with excellent visibility can be realized. For example, when the second phase difference member 22 satisfies such surface smoothness, the uniformity of the in-plane phase difference can be improved, and as a result, light leakage in the reflective portion described later can be suppressed. A method for measuring the surface smoothness will be described later.

[0025] The variation in thickness of the second phase difference member 22 is preferably 1 μm or less, more preferably 0.8 μm or less, further preferably 0.6 μm or less, and further preferably 0.4 μm or less. With such a variation in thickness, for example, the above-mentioned surface smoothness can be satisfactorily achieved.

[0026] The second phase difference member 22 is formed of any appropriate material that can satisfy the above characteristics. The second phase difference member 22 can be, for example, a stretched resin film or an oriented and solidified layer of a liquid crystal compound. The second phase difference member 22 composed of a stretched resin film or an oriented and solidified layer of a liquid crystal compound can be described in the same manner as the layer functioning as a λ / 4 plate constituting the first phase difference member 20 described in Section B. The layer functioning as a λ / 4 plate and the second phase difference member 22 may be members of the same configuration (forming material, thickness, optical properties, etc.) or may be members of different configurations.

[0027] The thickness of the second retardation member 22 is preferably 100 μm or less. Specifically, the thickness of the second retardation member 22 made of a stretched resin film is, for example, 10 μm to 100 μm, preferably 10 μm to 70 μm, more preferably 10 μm to 60 μm, and even more preferably 20 μm to 50 μm. The thickness of the second retardation member 22 made of a liquid crystal alignment solidified layer is, for example, 1 μm to 10 μm, preferably 1 μm to 8 μm, more preferably 1 μm to 6 μm, and even more preferably 1 μm to 4 μm.

[0028] The reflecting section 14 may include an absorptive polarizing member in addition to the reflective polarizing member. The absorptive polarizing member may be disposed in front of the reflective polarizing member. The reflection axis of the reflective polarizing member and the absorption axis of the absorptive polarizing member may be disposed approximately parallel to each other, and the transmission axis of the reflective polarizing member and the transmission axis of the absorptive polarizing member may be disposed approximately parallel to each other. When the reflecting section 14 includes an absorptive polarizing member, the reflecting section 14 may include a laminate having a reflective polarizing member and an absorptive polarizing member.

[0029] The reflective polarizing member can transmit light polarized parallel to its transmission axis (typically, linearly polarized light) while maintaining its polarization state, and can reflect light polarized in other states (typically, light polarized perpendicular to its transmission axis). The orthogonal transmittance (Tc) of the reflective polarizing member can be, for example, 0.01% to 3%. The single transmittance (Ts) of the reflective polarizing member can be, for example, 43% to 49%, preferably 45% to 47%. The polarization degree (P) of the reflective polarizing member can be, for example, 92% to 99.99%. The reflective polarizing member is typically composed of a film having a multilayer structure (sometimes referred to as a reflective polarizing film). Commercially available reflective polarizing films include, for example, 3M's product names "DBEF" and "APF" and Nitto Denko's product name "APCF".

[0030] The absorptive polarizing member may typically include a resin film containing a dichroic material (i.e., an absorptive polarizing film). As the absorptive polarizing film, the absorptive polarizing film described in Section B may be used. The thickness of the absorptive polarizing film is, for example, 1 μm or more and 20 μm or less, and may be 2 μm or more and 15 μm or less, 12 μm or less, 10 μm or less, 8 μm or less, or 5 μm or less.

[0031] B. Optical laminate FIG. 2 is a schematic cross-sectional view of an optical laminate according to one embodiment of the present invention. The optical laminate 200 includes a polarizing member 10, a layer 20a functioning as a λ / 2 plate, and a layer 20b functioning as a λ / 4 plate in this order. The optical laminate 200 is preferably used so that the layer 20b functioning as a λ / 4 plate is the viewing side. In one embodiment, the optical laminate can be used by being disposed on the display element side (for example, between the display element and the lens unit) in a display system such as VR goggles. As described above, in the display system, the polarizing member and the first phase difference member included in the display element can constitute the optical laminate. In other words, a laminate including the layer 20a functioning as a λ / 2 plate and the layer 20b functioning as a λ / 4 plate constitutes the first phase difference member 20.

[0032] By using the optical laminate of the above configuration, a display system with excellent display characteristics can be obtained. For example, in a display system including a lens section, by arranging the optical laminate in the optical path before reaching the lens section, light with high circular polarization can be introduced into the lens section of the display system, and as a result, the so-called ghost phenomenon in which display images are viewed overlapping can be reduced. In addition, light leakage can be suppressed, which can contribute to high definition. These effects become more pronounced by incorporating the optical laminate in the display system described in Section A.

[0033] In the optical laminate, the ellipticity of the transmitted light having a wavelength of 550 nm measured at a polar angle of 30° and an azimuth angle of 0° to 360° is preferably 0.77 or more, more preferably 0.78 or more, even more preferably 0.80 or more, even more preferably 0.82 or more, and particularly preferably 0.84 or more. If an optical laminate showing such an ellipticity is used, the above effect becomes remarkable. One of the results of the optical laminate is that the display characteristics can be improved by precisely controlling the ellipticity of the transmitted light in all directions. In the optical laminate, the higher the ellipticity of the transmitted light having a wavelength of 550 nm measured at a polar angle of 30° and an azimuth angle of 0° to 360°, the more preferable, and the upper limit is, for example, 0.90 (preferably 0.93, more preferably 0.95, and even more preferably 0.99). The ellipticity is the ratio of the minor axis / major axis of circularly polarized light, and for example, the ellipticity of completely circularly polarized light is 1, and the ellipticity of completely linearly polarized light is 0. In this specification, the term "ellipticity" means the absolute value of ellipticity.

[0034] In this specification, the ellipticity of transmitted light measured at a polar angle of 30° and azimuth angles of 0° to 360° refers to the ellipticity measured at every 11.25° azimuth angle in the range of 0° to 360° for light of a specific wavelength incident from the polarizing member side at a polar angle of 30° and outputting light at a polar angle of 30°. Therefore, "the ellipticity is X or more" measured at azimuth angles of 0° to 360° means that the minimum value of the 32 measured values ​​obtained is X.

[0035] In one embodiment, the optical laminate has an ellipticity of transmitted light having a wavelength of 450 nm measured at a polar angle of 30° and an azimuth angle of 0° to 360° of preferably 0.77 or more, more preferably 0.80 or more, even more preferably 0.82 or more, and particularly preferably 0.84 or more. Within such a range, an optical laminate having a remarkable effect of reducing ghost phenomenon, suppressing light leakage, and achieving high definition can be obtained. In the optical laminate, the higher the ellipticity of transmitted light having a wavelength of 450 nm measured at a polar angle of 30° and an azimuth angle of 0° to 360°, the more preferable, and the upper limit is, for example, 0.90 (preferably 0.93, more preferably 0.95, and even more preferably 0.99).

[0036] In one embodiment, the optical laminate has an ellipticity of transmitted light having a wavelength of 650 nm measured at a polar angle of 30° and an azimuth angle of 0° to 360° of preferably 0.77 or more, more preferably 0.80 or more, and even more preferably 0.82 or more. Within such a range, an optical laminate having a remarkable effect of reducing ghost phenomenon, suppressing light leakage, and achieving high definition can be obtained. In the optical laminate, the higher the ellipticity of transmitted light having a wavelength of 650 nm measured at a polar angle of 30° and an azimuth angle of 0° to 360°, the more preferable, and the upper limit is, for example, 0.90 (preferably 0.93, more preferably 0.95, and even more preferably 0.99).

[0037] In one embodiment, when the ellipticity of the transmitted light having a wavelength of 550 nm is measured at every azimuth angle of 11.25° in the range of 0° to 360° at a polar angle of 30°, the average value of the ellipticity is 0.83 or more, preferably 0.84 or more, and more preferably 0.86 or more. In such a range, an optical laminate having a remarkable effect of reducing ghost phenomenon, suppressing light leakage, and improving definition can be obtained. When the ellipticity of the transmitted light having a wavelength of 550 nm is measured at every azimuth angle of 11.25° in the range of 0° to 360° at a polar angle of 30°, the higher the average value of the ellipticity, the more preferable, but the upper limit is, for example, 0.90 (preferably 0.95). In this specification, the average value of the ellipticity means the average value of 32 measured values ​​obtained by measuring the ellipticity as described above.

[0038] In one embodiment, when the ellipticity of the transmitted light of wavelength 450 nm is measured at every azimuth angle of 11.25° in the range of 0° to 360° at a polar angle of 30°, the average value of the ellipticity is 0.80 or more, preferably 0.84 or more, and more preferably 0.86 or more. In such a range, an optical laminate having a remarkable effect of reducing ghost phenomenon, suppressing light leakage, and achieving high definition can be obtained. In the optical laminate, when the ellipticity of the transmitted light of wavelength 450 nm is measured at every azimuth angle of 11.25° in the range of 0° to 360° at a polar angle of 30°, the higher the average value of the ellipticity, the better, but the upper limit is, for example, 0.90 (preferably 0.95).

[0039] In one embodiment, when the ellipticity of the transmitted light of a wavelength of 650 nm is measured at every azimuth angle of 11.25° in the range of 0° to 360° at a polar angle of 30°, the average value of the ellipticity is 0.80 or more, preferably 0.84 or more, and more preferably 0.86 or more. In such a range, an optical laminate having a remarkable effect of reducing ghost phenomenon, suppressing light leakage, and achieving high definition can be obtained. In the optical laminate, when the ellipticity of the transmitted light of a wavelength of 650 nm is measured at every azimuth angle of 11.25° in the range of 0° to 360° at a polar angle of 30°, the higher the average value of the ellipticity, the more preferable, but the upper limit is, for example, 0.90 (preferably 0.95).

[0040] In one embodiment, when the ellipticity of transmitted light having a wavelength of 550 nm is measured at every azimuth angle of 11.25° in the range of azimuth angles from 0° to 360° at a polar angle of 30°, the optical laminate has 10 or more data points for which the ellipticity is 0.85 or more, preferably 15 or more data points, more preferably 20 or more data points, even more preferably 25 or more data points, particularly preferably 30 or more data points, and most preferably 32 data points. If the data points are within such a range, an optical laminate having a remarkable effect of reducing the ghost phenomenon, suppressing light leakage, and achieving high definition can be obtained.

[0041] In one embodiment, when the ellipticity of transmitted light having a wavelength of 450 nm is measured at every azimuth angle of 11.25° in the range of azimuth angles from 0° to 360° at a polar angle of 30°, the optical laminate has 10 or more data points for which the ellipticity is 0.85 or more, preferably 15 or more data points, more preferably 20 or more data points, even more preferably 25 or more data points, particularly preferably 30 or more data points, and most preferably 32 data points. If the data points are within such a range, an optical laminate having a remarkable effect of reducing ghost phenomenon, suppressing light leakage, and achieving high definition can be obtained.

[0042] In one embodiment, when the ellipticity of transmitted light of a wavelength of 650 nm is measured at every azimuth angle of 11.25° in the range of azimuth angles from 0° to 360° at a polar angle of 30°, the optical laminate has 10 or more data points for which the ellipticity is 0.85 or more, preferably 15 or more data points, more preferably 20 or more data points, even more preferably 25 or more data points, particularly preferably 30 or more data points, and most preferably 32 data points. If the data points are within such a range, an optical laminate having a remarkable effect of reducing the ghost phenomenon, suppressing light leakage, and achieving high definition can be obtained.

[0043] In one embodiment, the optical laminate has an ellipticity of 550 nm wavelength transmitted light measured at a polar angle of 0° (front direction) of preferably 0.94 or more, more preferably 0.95 or more, and even more preferably 0.96 or more. Within such a range, an optical laminate having a remarkable effect of reducing ghost phenomenon, suppressing light leakage, and achieving high definition can be obtained. The higher the ellipticity of 550 nm wavelength transmitted light measured at a polar angle of 0° (front direction) is, the more preferable it is, but the upper limit is, for example, 0.99 (preferably 1).

[0044] In one embodiment, the optical laminate has an ellipticity of 450 nm wavelength transmitted light measured at a polar angle of 0° (front direction) of preferably 0.94 or more, more preferably 0.95 or more, and even more preferably 0.96 or more. Within such a range, an optical laminate having a remarkable effect of reducing ghost phenomenon, suppressing light leakage, and achieving high definition can be obtained. The higher the ellipticity of 450 nm wavelength transmitted light measured at a polar angle of 0° (front direction) is, the more preferable it is, but the upper limit is, for example, 0.99 (preferably 1).

[0045] In one embodiment, the optical laminate has an ellipticity of 650 nm wavelength transmitted light measured at a polar angle of 0° (front direction) of preferably 0.94 or more, more preferably 0.95 or more, and even more preferably 0.96 or more. Within such a range, an optical laminate having a remarkable effect of reducing ghost phenomenon, suppressing light leakage, and achieving high definition can be obtained. The higher the ellipticity of 650 nm wavelength transmitted light measured at a polar angle of 0° (front direction) is, the more preferable it is, and the upper limit is, for example, 0.99 (preferably 1).

[0046] In the above optical laminate, the ratio (ellipticity B / ellipticity A) of "the average value of ellipticity when the ellipticity of transmitted light of wavelength 550 nm is measured at every azimuth angle of 11.25° in the range of azimuth angles 0° to 360° at a polar angle of 30°" (ellipticity B) to "the ellipticity of transmitted light of wavelength 550 nm measured at a polar angle of 0° (front direction)" (ellipticity A) is preferably 0.85 or more, more preferably 0.88 or more, and more preferably 0.9 or more. Within such a range, an optical laminate having a remarkable effect of reducing the ghost phenomenon, suppressing light leakage, and achieving high definition can be obtained. The upper limit of ellipticity B / ellipticity A is, for example, 0.98 (preferably 0.99, more preferably 1).

[0047] In one embodiment, the depolarization index (DI) of the optical laminate is 1 minus (1-DI) and is 60% or more. The depolarization index can be calculated by measuring the Mueller matrix (below (1)) representing the polarization effect and using the following formula (2). The Mueller matrix representing the polarization effect is measured, for example, by using a Mueller matrix polarimeter (manufactured by Axometrics, product name "Axoscan") at 23°C, by irradiating light of a predetermined wavelength (for example, 550 nm) from the polarizing member side of the optical laminate.

number

[0048] The optical laminate has a depolarization index (DI) of transmitted light having a wavelength of 550 nm measured at a polar angle of 30° and an azimuth angle of 0° to 360°, which is preferably 99.4% or more, more preferably 99.5% or more, even more preferably 99.6% or more, and particularly preferably 99.68% or more, obtained by subtracting from 1 the depolarization index (DI) of transmitted light having a wavelength of 550 nm measured at a polar angle of 30° and an azimuth angle of 0° to 360°. If the DI is within such a range, the effect of the present invention becomes remarkable. In this specification, the depolarization index (DI) of a predetermined wavelength measured at a polar angle of 30° and an azimuth angle of 0° to 360° is the average value of the depolarization index measured at every azimuth angle of 11.25° in the range of azimuth angles of 0° to 360° for light emitted at a polar angle of 30° by making light of a predetermined wavelength incident on the polarizing member side of the optical laminate.

[0049] The optical laminate has a depolarization index (DI) of 450 nm wavelength transmitted light measured at a polar angle of 30° and an azimuth angle of 0° to 360° minus 1 (1-DI) of preferably 99.4% or more, more preferably 99.5% or more, and even more preferably 99.6% or more. If the DI is within such a range, the effect of the present invention becomes remarkable.

[0050] The optical laminate has a depolarization index (DI) of 650 nm wavelength transmitted light measured at a polar angle of 30° and an azimuth angle of 0° to 360° minus 1 (1-DI) of preferably 99.4% or more, more preferably 99.5%, and even more preferably 99.6% or more. If the DI is within such a range, the effect of the present invention becomes remarkable.

[0051] The optical laminate has a depolarization index (DI) of 550 nm wavelength transmitted light measured at a polar angle of 0° (front direction) subtracted from 1 (1-DI) of preferably 99.5% or more, more preferably 99.6% or more, even more preferably 99.7% or more, and particularly preferably 99.75% or more. If the DI is within such a range, the effect of the present invention becomes remarkable.

[0052] The optical laminate has a depolarization index (DI) of 450 nm wavelength transmitted light measured at a polar angle of 0° (front direction) subtracted from 1 (1-DI) of preferably 99.5% or more, more preferably 99.6% or more, and even more preferably 99.7% or more. If the DI is within such a range, the effect of the present invention becomes remarkable.

[0053] The optical laminate has a depolarization index (DI) of 650 nm wavelength transmitted light measured at a polar angle of 0° (front direction) subtracted from 1 (1-DI) of preferably 99.4% or more, more preferably 99.5% or more, and even more preferably 99.6% or more. If the DI is within such a range, the effect of the present invention becomes remarkable.

[0054] (Phase difference material) As described above, the optical laminate includes, as retardation members, a layer functioning as a λ / 2 plate and a layer functioning as a λ / 4 plate, in this order from the polarizing member side.

[0055] The angle between the slow axis of the layer functioning as a λ / 2 plate and the absorption axis of the polarizing member is preferably 5° to 35°, more preferably 10° to 20°, even more preferably 12° to 18°, and particularly preferably about 15°. The angle between the slow axis of the layer functioning as a λ / 4 plate and the absorption axis of the polarizing member is preferably 55° to 85°, more preferably 70° to 80°, even more preferably 72° to 78°, and particularly preferably about 75°.

[0056] The in-plane retardation Re(550) of the layer functioning as a λ / 4 plate is, for example, 100 nm to 200 nm, or may be 110 nm to 180 nm, 130 nm to 160 nm, or may be 135 nm to 155 nm.

[0057] The in-plane retardation Re(550) of the layer functioning as a λ / 2 plate is, for example, 200 nm to 330 nm, or may be 230 nm to 330 nm, 230 nm to 290 nm, or may be 250 nm to 280 nm.

[0058] The layer functioning as a λ / 4 plate preferably exhibits an inverse dispersion wavelength characteristic in which the phase difference value increases according to the wavelength of the measurement light. The Re(450) / Re(550) of the layer constituting the retardation member is, for example, less than 1, and may be 0.95 or less, and may further be less than 0.90, and further may be 0.85 or less. The Re(450) / Re(550) of the layer constituting the retardation member is, for example, 0.75 or more. The layer functioning as a λ / 2 plate preferably exhibits an inverse dispersion wavelength characteristic in which the phase difference value increases according to the wavelength of the measurement light. The Re(450) / Re(550) of the layer constituting the retardation member is, for example, less than 1, and may be 0.95 or less, and may further be less than 0.90, and further may be 0.85 or less. The Re(450) / Re(550) of the layer constituting the retardation member is, for example, 0.75 or more. Hereinafter, the layer functioning as a λ / 4 plate and the layer functioning as a λ / 2 plate may be collectively referred to as the layer constituting the retardation member.

[0059] In one embodiment, the layers constituting the retardation member satisfy all of Re(400) / Re(550) < 0.85, Re(650) / Re(550) > 1.03, and Re(750) / Re(550) > 1.05. The layers constituting the retardation member preferably satisfy at least one selected from 0.65 < Re(400) / Re(550) < 0.80 (preferably, 0.7 < Re(400) / Re(550) < 0.75), 1.0 < Re(650) / Re(550) < 1.25 (preferably, 1.05 < Re(650) / Re(550) < 1.20), and 1.05 < Re(750) / Re(550) < 1.40 (preferably, 1.08 < Re(750) / Re(550) < 1.36), more preferably satisfy at least two, and still more preferably satisfy all of them.

[0060] The layers constituting the retardation member in the optical laminate preferably exhibit a refractive index characteristic of nx > ny ≧ nz. Here, "ny = nz" includes not only the case where ny and nz are exactly equal but also the case where they are substantially equal. Therefore, within a range that does not impair the effects of the present invention, ny < nz may occur. The Nz coefficient of the layers constituting the retardation member in the optical laminate is preferably 0.9 to 3, more preferably 0.9 to 2.5, still more preferably 0.9 to 1.5, and particularly preferably 0.9 to 1.3.

[0061] The surface smoothness of the layers constituting the retardation member in the optical laminate is, for example, 0.50 arcmin or less, preferably 0.40 arcmin or less, more preferably 0.30 arcmin or less, and still more preferably 0.20 arcmin or less. Within such a range, a display system with excellent visibility can be realized. For example, by satisfying such surface smoothness, the in-plane retardation uniformity can be improved, and as a result, a display system having excellent display characteristics can be obtained.

[0062] The thickness variation of the layers constituting the retardation member in the optical laminate is preferably 1 μm or less, more preferably 0.8 μm or less, even more preferably 0.6 μm or less, and even more preferably 0.4 μm or less. Such thickness variation can, for example, achieve the above-mentioned surface smoothness well. Here, the thickness variation can be obtained by measuring the thickness of a first portion located in the measurement surface and the thickness of a position spaced a predetermined distance (for example, 5 mm to 15 mm) from the first portion in any direction (for example, upward, downward, leftward, and rightward).

[0063] The layer constituting the retardation member in the optical laminate is formed of any suitable material that can satisfy the above characteristics. The retardation member can be, for example, a stretched film of a resin film or an oriented and solidified layer of a liquid crystal compound. The stretched film of a resin film may be referred to as a retardation film.

[0064] Examples of the resin contained in the resin film include polycarbonate-based resins, polyester carbonate-based resins, polyester-based resins, polyvinyl acetal-based resins, polyarylate-based resins, cyclic olefin-based resins, cellulose-based resins, polyvinyl alcohol-based resins, polyamide-based resins, polyimide-based resins, polyether-based resins, polystyrene-based resins, and acrylic-based resins. These resins may be used alone or in combination (for example, blended or copolymerized). When the layer constituting the retardation member in the optical laminate shows reverse dispersion wavelength characteristics, a resin film containing a polycarbonate-based resin or a polyester carbonate-based resin (hereinafter, sometimes simply referred to as a polycarbonate-based resin) can be suitably used.

[0065] As the polycarbonate-based resin, any suitable polycarbonate-based resin can be used as long as the effects of the present invention can be obtained. For example, the polycarbonate-based resin contains a structural unit derived from a fluorene-based dihydroxy compound, a structural unit derived from an isosorbide-based dihydroxy compound, and a structural unit derived from at least one dihydroxy compound selected from the group consisting of an alicyclic diol, an alicyclic dimethanol, a di-, tri- or polyethylene glycol, and an alkylene glycol or a spiro glycol. Preferably, the polycarbonate-based resin contains a structural unit derived from a fluorene-based dihydroxy compound, a structural unit derived from an isosorbide-based dihydroxy compound, a structural unit derived from an alicyclic dimethanol, and / or a structural unit derived from a di-, tri- or polyethylene glycol; more preferably, it contains a structural unit derived from a fluorene-based dihydroxy compound, a structural unit derived from an isosorbide-based dihydroxy compound, and a structural unit derived from a di-, tri- or polyethylene glycol. The polycarbonate-based resin may contain a structural unit derived from another dihydroxy compound as necessary. Details of polycarbonate-based resins that can be suitably used in the layers constituting the first phase difference member and methods for forming the layers constituting the first phase difference member are described in, for example, JP 2014-10291 A, JP 2014-26266 A, JP 2015-212816 A, JP 2015-212817 A, and JP 2015-212818 A, and the descriptions in these publications are incorporated herein by reference.

[0066] When a layer functioning as a λ / 4 plate is formed from a stretched film, the thickness is, for example, 10 μm to 100 μm, preferably 10 μm to 70 μm, more preferably 10 μm to 60 μm, and even more preferably 20 μm to 50 μm.When a layer functioning as a λ / 2 plate is formed from a stretched film, the thickness is, for example, 20 μm to 200 μm, preferably 20 μm to 140 μm, more preferably 20 μm to 120 μm, and even more preferably 40 μm to 100 μm.

[0067] The above-mentioned liquid crystal compound alignment solidified layer is a layer in which the liquid crystal compound is aligned in a predetermined direction within the layer, and the alignment state is fixed. The "alignment solidified layer" is a concept that includes an alignment solidified layer obtained by solidifying a liquid crystal monomer as described later. Typically, rod-shaped liquid crystal compounds are aligned in the slow axis direction of a layer (e.g., a layer functioning as a λ / 4 plate, a layer functioning as a λ / 2 plate, etc.) constituting a retardation member in an optical laminate (homogeneous alignment). Examples of rod-shaped liquid crystal compounds include liquid crystal polymers and liquid crystal monomers. The liquid crystal compound is preferably polymerizable. If the liquid crystal compound is polymerizable, the alignment state of the liquid crystal compound can be fixed by aligning the liquid crystal compound and then polymerizing it.

[0068] The alignment solidified layer of the liquid crystal compound (liquid crystal alignment solidified layer) can be formed by performing an alignment treatment on the surface of a predetermined substrate, applying a coating liquid containing a liquid crystal compound to the surface to align the liquid crystal compound in a direction corresponding to the alignment treatment, and fixing the alignment state. Any appropriate alignment treatment can be adopted as the alignment treatment. Specifically, mechanical alignment treatment, physical alignment treatment, and chemical alignment treatment can be mentioned. Specific examples of mechanical alignment treatment include rubbing treatment and stretching treatment. Specific examples of physical alignment treatment include magnetic field alignment treatment and electric field alignment treatment. Specific examples of chemical alignment treatment include oblique deposition method and photoalignment treatment. As the treatment conditions of various alignment treatments, any appropriate conditions can be adopted depending on the purpose.

[0069] The alignment of the liquid crystal compound is performed by treating the liquid crystal compound at a temperature at which the liquid crystal compound exhibits a liquid crystal phase according to the type of liquid crystal compound. By performing such temperature treatment, the liquid crystal compound takes on a liquid crystal state and is aligned according to the alignment treatment direction of the substrate surface.

[0070] In one embodiment, the alignment state is fixed by cooling the liquid crystal compound aligned as described above. When the liquid crystal compound is polymerizable or crosslinkable, the alignment state is fixed by subjecting the liquid crystal compound aligned as described above to a polymerization treatment or crosslinking treatment.

[0071] As the liquid crystal compound, any suitable liquid crystal polymer and / or liquid crystal monomer is used. The liquid crystal polymer and the liquid crystal monomer may be used alone or in combination. Specific examples of the liquid crystal compound and the method for producing the liquid crystal alignment solidified layer are described in, for example, JP 2006-163343 A, JP 2006-178389 A, and WO 2018 / 123551 A. The descriptions in these publications are incorporated herein by reference.

[0072] When a layer functioning as a λ / 4 plate is formed from an oriented and solidified layer of a liquid crystal compound, the thickness is, for example, 1 μm to 10 μm, preferably 1 μm to 8 μm, more preferably 1 μm to 6 μm, and even more preferably 1 μm to 4 μm.When a layer functioning as a λ / 2 plate is formed from an oriented and solidified layer of a liquid crystal compound, the thickness is, for example, 2 μm to 20 μm, preferably 2 μm to 16 μm, more preferably 2 μm to 12 μm, and even more preferably 2 μm to 8 μm.

[0073] (Polarizing material) The polarizing member may typically include a resin film (sometimes referred to as an absorptive polarizing film) containing a dichroic material. The thickness of the absorptive polarizing film is, for example, 1 μm or more and 20 μm or less, and may be 2 μm or more and 15 μm or less, 12 μm or less, 10 μm or less, 8 μm or less, or 5 μm or less.

[0074] The polarizing member may be made of a single-layer resin film, or may be made of a laminate of two or more layers.

[0075] When producing a polarizing member from a single-layer resin film, for example, a hydrophilic polymer film such as a polyvinyl alcohol (PVA)-based film, a partially formalized PVA-based film, or an ethylene-vinyl acetate copolymer-based partially saponified film can be dyed with iodine or a dichroic substance such as a dichroic dye, stretched, etc. to obtain a polarizing member. Among these, a polarizing member obtained by dyeing a PVA-based film with iodine and uniaxially stretching it is preferred.

[0076] The dyeing with iodine is carried out, for example, by immersing the PVA film in an aqueous iodine solution. The stretching ratio of the uniaxial stretching is preferably 3 to 7 times. The stretching may be carried out after the dyeing treatment or while the dyeing is being carried out. Alternatively, the stretching may be followed by dyeing. If necessary, the PVA film is subjected to a swelling treatment, a crosslinking treatment, a washing treatment, a drying treatment, or the like.

[0077] Examples of the laminate produced using the laminate of two or more layers include a laminate of a resin substrate and a PVA-based resin layer (PVA-based resin film) laminated on the resin substrate, or a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate. The absorptive polarizing film obtained using a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate can be produced, for example, by coating a PVA-based resin solution on the resin substrate and drying the resin substrate to form a PVA-based resin layer on the resin substrate to obtain a laminate of the resin substrate and the PVA-based resin layer; and stretching and dyeing the laminate to make the PVA-based resin layer into an absorptive polarizing film. In this embodiment, preferably, a polyvinyl alcohol-based resin layer containing a halide and a polyvinyl alcohol-based resin is formed on one side of the resin substrate. The stretching typically includes immersing the laminate in an aqueous boric acid solution to stretch it. Furthermore, the stretching may further include, as necessary, stretching the laminate in air at a high temperature (for example, 95° C. or higher) before stretching in the aqueous boric acid solution. In addition, in this embodiment, the laminate is preferably subjected to a drying shrinkage treatment in which the laminate is heated while being transported in the longitudinal direction, thereby shrinking the laminate by 2% or more in the width direction. Typically, the manufacturing method of this embodiment includes subjecting the laminate to an air-assisted stretching treatment, a dyeing treatment, an underwater stretching treatment, and a drying shrinkage treatment in this order. By introducing the auxiliary stretching, even when PVA is applied onto a thermoplastic resin, it is possible to increase the crystallinity of PVA, and to achieve high optical properties. At the same time, by increasing the orientation of PVA in advance, problems such as a decrease in the orientation or dissolution of PVA when immersed in water in the subsequent dyeing and stretching steps can be prevented, and high optical properties can be achieved. Furthermore, when the PVA-based resin layer is immersed in a liquid, the disorder of the orientation of polyvinyl alcohol molecules and the decrease in the orientation can be suppressed compared to when the PVA-based resin layer does not contain a halide. This can improve the optical properties of the absorptive polarizing film obtained through treatment steps in which the laminate is immersed in a liquid, such as a dyeing treatment and an underwater stretching treatment. Furthermore, the optical properties can be improved by shrinking the laminate in the width direction through drying shrinkage treatment.The obtained laminate of resin substrate / absorptive polarizing film may be used as it is (i.e., the resin substrate may be used as a protective layer for the absorptive polarizing film), or any suitable protective layer may be laminated on the peeled surface of the resin substrate / absorptive polarizing film laminate after peeling the resin substrate from the laminate, or on the surface opposite to the peeled surface, depending on the purpose. Details of the method for producing such an absorptive polarizing film are described in, for example, JP2012-73580A and JP6470455A. The entire disclosures of these publications are incorporated herein by reference.

[0078] The crossed transmittance (Tc) of the absorptive polarizing film is preferably 0.5% or less, more preferably 0.1% or less, and further preferably 0.05% or less. The single transmittance (Ts) of the absorptive polarizing film is, for example, 41.0% to 45.0%, and preferably 42.0% or more. The polarization degree (P) of the absorptive polarizing film is, for example, 99.0% to 99.997%, and preferably 99.9% or more.

[0079] (Other materials) Each member constituting the optical laminate can be laminated via any suitable adhesive layer. By laminating the members via an adhesive layer, an optical laminate having excellent smoothness can be obtained. If the display system described in section A is constructed using the optical laminate having excellent smoothness, for example, an image display having excellent display characteristics can be realized even if the image is enlarged by the lens unit.

[0080] In one embodiment, the phase difference member in the optical laminate has any suitable adhesive layer, and the layers constituting the phase difference member in the optical laminate can be laminated through the adhesive layer.In addition, the phase difference member and the polarizing member can be laminated through the adhesive layer.By integrating the phase difference member and the polarizing member with the adhesive layer, it is possible to obtain an optical laminate that can contribute to preventing the ghost phenomenon.

[0081] The adhesive layer may be formed of an adhesive or a pressure-sensitive adhesive. Specifically, the adhesive layer may be an adhesive layer or a pressure-sensitive adhesive layer. The thickness of the adhesive layer is, for example, 0.05 μm to 30 μm.

[0082] Specific examples of the adhesive include acrylic adhesives, rubber adhesives, silicone adhesives, polyester adhesives, urethane adhesives, epoxy adhesives, and polyether adhesives. By adjusting the type, number, combination, and compounding ratio of the monomers forming the base resin of the adhesive, as well as the compounding amount of the crosslinking agent, reaction temperature, reaction time, etc., an adhesive having desired properties according to the purpose can be prepared. The base resin of the adhesive may be used alone or in combination of two or more. As the base resin, an acrylic resin is preferably used.

[0083] The adhesive irreversibly changes from a liquid to a solid state during the process of forming the adhesive layer, has fluidity when applied, and has the property of being cured by a curing treatment (e.g., irradiation with active energy rays, heating). As the adhesive, a curable adhesive is preferably used. Specifically, the adhesive layer is preferably a cured layer of a resin. As the curable adhesive, an ultraviolet-curable adhesive is preferably used.

[0084] The ultraviolet-curable adhesive contains a curable monomer such as a compound having a (meth)acryloyl group or a compound having a vinyl group. A compound having a (meth)acryloyl group is preferably used. Here, the (meth)acryloyl group refers to an acryloyl group and / or a methacryloyl group.

[0085] The thickness of the adhesive layer included in the retardation member is, for example, 0.5 μm or more and 3 μm or less, preferably 2 μm or less, more preferably 1.3 μm or less, further preferably 1.1 μm or less, and particularly preferably 0.9 μm or less. With such a thickness, an optical laminate having extremely excellent smoothness can be obtained.

[0086] The optical laminate may further include a member (so-called positive C plate) whose refractive index characteristics can show the relationship nz>nx=ny. The positive C plate may be arranged, for example, on the opposite side of the retardation member to the polarizing member (i.e., the opposite side of the layer functioning as a λ / 4 plate to the layer functioning as a λ / 2 plate). By arranging the positive C plate, an optical laminate having a higher ellipticity of the emitted light can be obtained.

[0087] The positive C plate has a thickness retardation Rth(550) of preferably -20nm to -200nm, more preferably -30nm to -180nm, further preferably -40nm to -160nm, and particularly preferably -50nm to -140nm. Here, "nx=ny" includes not only the case where nx and ny are strictly equal, but also the case where nx and ny are substantially equal. The positive C plate has an in-plane retardation Re(550) of, for example, less than 10nm.

[0088] The positive C plate is made of any suitable material that can satisfy the above characteristics. The positive C plate can be, for example, a resin film or an alignment solidified layer of a liquid crystal compound.

[0089] Representative materials for the resin film constituting the positive C plate include resin materials having negative birefringence. A resin having negative birefringence is a resin that exhibits a property that the refractive index in the direction perpendicular to the stretching direction is maximized when uniaxially stretched. Examples of resins having negative birefringence include resins in which a chemical bond or functional group with large polarization anisotropy, such as an aromatic ring or a carbonyl group, is introduced into the side chain. Specific examples of resins having negative birefringence include acrylic resins, styrene resins, maleimide resins, modified polyolefin resins, fumaric acid ester resins, etc., and specific examples thereof include resins having negative birefringence described in JP-A-2021-076759, JP-T-2008-544304, JP-T-2008-544317, etc. can be referred to. The above resin materials can be used alone or in combination of two or more kinds.

[0090] The resin film constituting the positive C plate may further contain any appropriate additives as necessary. Specific examples of the additives include plasticizers, heat stabilizers, light stabilizers, lubricants, antioxidants, ultraviolet absorbers, flame retardants, colorants, antistatic agents, compatibilizers, crosslinking agents, thickeners, etc. The type and content of the additives may be appropriately set depending on the purpose. The content of the additives in the resin film is, for example, about 3% by weight to 10% by weight.

[0091] In one embodiment, the resin material can be used as a positive C plate as it is after it is formed into a film. Specifically, the formed film can be used as a positive C plate as it is without stretching. For example, when a resin solution containing the resin material is applied to a support to form a film (by a solution film-forming method), stress occurs due to volume shrinkage when the resin solution is dried on the support, and the molecular chains of the polymer tend to be oriented in the in-plane direction. When a resin material having high birefringence expression and negative intrinsic birefringence is used, a coating film having large thickness direction birefringence can be formed on the support due to the shrinkage action during drying. The formed coating film can be used as a positive C plate as it is.

[0092] The thickness of the positive C plate made of a resin film is, for example, 1 μm to 40 μm, preferably 3 μm to 35 μm, and more preferably 5 μm to 30 μm.

[0093] A preferred example of the alignment and solidification layer of the liquid crystal compound constituting the positive C plate is an alignment and solidification layer of a liquid crystal material fixed in homeotropic alignment. The liquid crystal material (liquid crystal compound) that can be homeotropically aligned may be a liquid crystal monomer or a liquid crystal polymer. Specific examples of such liquid crystal compounds and methods for forming a positive C plate include the liquid crystal compounds and methods for forming the retardation layer described in

[0020] to

[0028] of JP-A-2002-333642.

[0094] The thickness of the positive C plate constituted by an aligned and solidified layer of a liquid crystal compound is preferably 0.5 μm to 10 μm, more preferably 0.5 μm to 8 μm, and further preferably 0.5 μm to 5 μm.

[0095] The optical laminate may include a protective member. The protective member may be disposed on the outermost side opposite to the polarizing member. In one embodiment, the protective member is an anti-reflection protective member.

[0096] The protective member is preferably composed of a laminated film having a substrate and a surface treatment layer formed on the substrate. The thickness of the laminated film is preferably 10 μm to 80 μm, more preferably 15 μm to 60 μm, and even more preferably 20 μm to 45 μm. The thickness of the surface treatment layer is preferably 0.5 μm to 10 μm, more preferably 1 μm to 7 μm, and even more preferably 2 μm to 5 μm.

[0097] The surface treatment layer typically includes a hard coat layer. The hard coat layer is typically formed by applying a hard coat layer-forming material to a substrate and curing the applied layer. The hard coat layer-forming material typically includes a curable compound as a layer-forming component. The curing mechanism of the curable compound may be, for example, a thermosetting type or a photocurable type. The curable compound may be, for example, a monomer, an oligomer, or a prepolymer. Preferably, a polyfunctional monomer or oligomer is used as the curable compound. The polyfunctional monomer or oligomer may be, for example, a monomer or oligomer having two or more (meth)acryloyl groups, a urethane (meth)acrylate or an oligomer of a urethane (meth)acrylate, an epoxy-based monomer or oligomer, or a silicone-based monomer or oligomer.

[0098] The thickness of the hard coat layer is preferably 0.5 μm to 10 μm, more preferably 1 μm to 7 μm, and further preferably 2 μm to 5 μm.

[0099] The surface treatment layer preferably includes a functional layer. The functional layer preferably functions as an antireflection layer. The protective member including the antireflection layer may be the antireflection protective member. In a preferred embodiment, the surface treatment layer includes the hard coat layer and the antireflection layer in this order from the substrate side. The thickness of the functional layer is preferably 0.05 μm to 10 μm, more preferably 0.1 μm to 5 μm, and even more preferably 0.1 μm to 2 μm.

[0100] The protective member having the surface treatment layer may be arranged so that the surface treatment layer is located on the front side. Specifically, the surface treatment layer may be located on the outermost surface of the optical laminate. In one embodiment, the surface treatment layer side surface of the protective member has a maximum value of 5° regular reflectance spectrum in the wavelength range of 420 nm to 680 nm of 2.0% or less, more preferably 1.2% or less, even more preferably 1.0% or less, and particularly preferably 0.8% or less. Here, the 5° regular reflectance can be measured, for example, by attaching the measurement target to a black acrylic plate using an adhesive to prepare a measurement sample, using a spectrophotometer (manufactured by Hitachi High-Technologies Corporation, product name "U-4100") as the measurement device, and setting the incident angle of light to the measurement sample to 5°. EXAMPLES

[0101] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples. The test and evaluation methods in the examples are as follows. The term "parts" means "parts by weight" unless otherwise specified, and the term "%" means "% by weight" unless otherwise specified.

[0102] (1) Thickness The thickness of 10 μm or less was measured using a scanning electron microscope (manufactured by JEOL, product name "JSM-7100F"), and the thickness of more than 10 μm was measured using a digital micrometer (manufactured by Anritsu, product name "KC-351C"). (2) In-plane phase difference Re(λ) The retardation film was cut from the center and both ends in the width direction to prepare a square sample with a width of 50 mm and a length of 50 mm, with one side parallel to the width direction of the film. The in-plane retardation of the sample was measured at each wavelength at 23°C using a Mueller matrix polarimeter (Axometrics, product name "Axoscan"). (3) Single transmittance and polarization degree of polarizing film The polarizing film was measured for its single transmittance Ts, parallel transmittance Tp, and crossed transmittance Tc using a spectrophotometer (Otsuka Electronics Co., Ltd., "LPF-200"). These Ts, Tp, and Tc are Y values ​​measured using a 2-degree visual field (C light source) according to JIS Z8701 and corrected for visibility. The degree of polarization of the polarizing film was calculated from the obtained Tp and Tc using the following formula. Degree of polarization (%)={(Tp-Tc) / (Tp+Tc)} 1 / 2 ×100 (4) Surface smoothness The smoothness of the retardation film was measured using a phase-shifting laser interferometer (manufactured by Zygo, product name "DynaFiz"). Specifically, the retardation film was laminated onto a microslide glass (manufactured by Matsunami Glass Industry, product name "S200200") so as to prevent the inclusion of foreign matter, air bubbles, or deformation lines. Next, degassing was performed using a pressurized degassing device (autoclave) to remove the effects of minute air bubbles. The degassing conditions were 50°C, 0.5 MPa, and 30 minutes. After degassing, the sample was allowed to cool at room temperature for 30 minutes or more to obtain a measurement sample. The sample was placed on a vibration-proof measuring table, and a single-wavelength (633 nm) laser was used to interfere with a standard with guaranteed flatness, and the relative displacement within a specified area (a circle of 30 mm diameter) was measured. For the analysis, the smoothness of the retardation film (unit: arcmin) was defined as double the "slope magnitude RMS" (equivalent to 2σ), which is an index of the angle obtained by extracting the frequency values ​​from 0.1 / mm to 1 / mm.

[0103] [Production Example 1-1: Preparation of Retardation Film 1] Into a batch polymerization apparatus consisting of two vertical reactors equipped with stirring blades and reflux condensers controlled at 100°C, 29.60 parts by weight (0.046 mol) of bis[9-(2-phenoxycarbonylethyl)fluoren-9-yl]methane, 29.21 parts by weight (0.200 mol) of isosorbide (ISB), 42.28 parts by weight (0.139 mol) of spiroglycol (SPG), 63.77 parts by weight (0.298 mol) of diphenyl carbonate (DPC), and 1.19 x 10 calcium acetate monohydrate as a catalyst were added. -2 Weight part (6.78×10 -5 mol) was charged. After the inside of the reactor was purged with nitrogen under reduced pressure, heating was performed with a heat medium, and stirring was started when the inside temperature reached 100 ° C. 40 minutes after the start of the temperature increase, the inside temperature was reached 220 ° C., and while controlling to maintain this temperature, the pressure was reduced and 90 minutes after reaching 220 ° C., the pressure was reduced to 13.3 kPa. Phenol vapor by-produced with the polymerization reaction was led to a reflux condenser at 100 ° C., a small amount of monomer components contained in the phenol vapor were returned to the reactor, and the uncondensed phenol vapor was led to a condenser at 45 ° C. and recovered. Nitrogen was introduced into the first reactor to restore the pressure to atmospheric pressure, and the oligomerized reaction liquid in the first reactor was transferred to the second reactor. Next, the temperature increase and pressure reduction in the second reactor were started, and the inside temperature was set to 240 ° C. and the pressure to 0.2 kPa in 50 minutes. Thereafter, polymerization was allowed to proceed until the specified stirring power was reached. When the predetermined power was reached, nitrogen was introduced into the reactor to restore pressure, and the produced polyester carbonate resin was extruded into water and the strands were cut to obtain pellets. The obtained polyester carbonate resin (pellets) was vacuum-dried at 80°C for 5 hours, and then a long resin film having a thickness of 130 μm was produced using a film-forming device equipped with a single-screw extruder (manufactured by Toshiba Machine Co., Ltd., cylinder setting temperature: 250°C), a T-die (width 200 mm, setting temperature: 250°C), a chill roll (setting temperature: 120 to 130°C) and a winder. The obtained long resin film was stretched in the width direction at a stretching temperature of 140°C and a stretching ratio of 2.7 times. In this way, a retardation film 1 (λ / 4 plate) having a thickness of 47 μm, Re(590) of 140 nm, and Nz coefficient of 1.2 was obtained. The obtained retardation film 1 had Re(450) / Re(550) of 0.856 and showed inverse dispersion wavelength characteristics. The surface smoothness of the film was 0.25 arcmin.

[0104] [Production Example 1-2: Preparation of Retardation Film 2] A polyester carbonate resin (pellets) was obtained in the same manner as in Production Example 1-1. The obtained polyester carbonate resin (pellets) was vacuum-dried at 80°C for 5 hours, and then a long resin film having a thickness of 260 μm was produced using a film-forming device equipped with a single-screw extruder (manufactured by Toshiba Machine Co., Ltd., cylinder set temperature: 250°C), a T-die (width 200 mm, set temperature: 250°C), a chill roll (set temperature: 120 to 130°C) and a winder. The obtained long resin film was stretched in the width direction at a stretching temperature of 140°C and a stretching ratio of 2.7 times. In this way, a retardation film 2 (λ / 2 plate) having a thickness of 91 μm, Re(590) of 270 nm, and Nz coefficient of 1.2 was obtained. The obtained retardation film 2 had Re(450) / Re(550) of 0.859 and showed inverse dispersion wavelength characteristics. The surface smoothness of the film was 0.35 arcmin.

[0105] [Production Example 1-3: Preparation of Retardation Layer (Liquid Crystal Compound Alignment Layer) 3] 55 parts by weight of the compound represented by formula (I), 25 parts by weight of the compound represented by formula (II), and 20 parts by weight of the compound represented by formula (III) were added to 400 parts by weight of cyclopentanone (CPN), and then heated to 60°C and stirred to dissolve. Then, the solution of the above-mentioned compound was returned to room temperature, and 3 parts by weight of Irgacure 907 (manufactured by BASF Japan Ltd.), 0.2 parts by weight of Megafac F-554 (manufactured by DIC Corporation), and 0.1 parts by weight of p-methoxyphenol (MEHQ) were added to the solution of the above-mentioned compound, and further stirred. The solution after stirring was transparent and uniform. The obtained solution was filtered through a 0.20 μm membrane filter to obtain a polymerizable composition. Also, a polyimide solution for an alignment film was applied to a glass substrate having a thickness of 0.7 mm by spin coating, and a coating film was obtained by drying at 100° C. for 10 minutes and then baking at 200° C. for 60 minutes. The obtained coating film was subjected to a rubbing treatment using a commercially available rubbing device to form an alignment film. Next, the polymerizable composition obtained above was applied to the substrate (substantially the alignment film) by spin coating, and dried at 100° C. for 2 minutes. After the obtained coating film was cooled to room temperature, it was heated with a high-pressure mercury lamp at 30 mW / cm 2 The film was irradiated with ultraviolet light at an intensity of 100 nm for 30 seconds to obtain a retardation layer (thickness: 3 μm) which is an alignment and solidification layer of the liquid crystal compound. The in-plane retardation Re(590) of the retardation layer was 140 nm. The retardation layer also had a Re(450) / Re(550) of 0.851, which showed reverse dispersion wavelength characteristics. This retardation layer can function as a λ / 4 plate. The surface smoothness of the retardation layer was 0.16 arcmin.

[0106] [ka] [ka]

[0107] [Production Example 1-4: Preparation of Retardation Layer (Liquid Crystal Compound Alignment Layer) 4] A retardation layer was obtained in the same manner as in Manufacturing Example 1-3, except that the thickness of the retardation layer was 6 μm. The in-plane retardation Re(590) of this retardation layer was 270 nm. In addition, the Re(450) / Re(550) of this retardation layer was 0.851, and it showed reverse dispersion wavelength characteristics. This retardation layer can function as a λ / 2 plate. The surface smoothness of the retardation layer was 0.22 arcmin.

[0108] [Production Example 1-5: Preparation of Retardation Film 5] A long norbornene resin film (manufactured by Zeon Corporation, product name Zeonor, thickness 40 μm) was stretched at a stretching ratio and stretching temperature so that the in-plane retardation Re (590) was 140 nm, and the free end was stretched longitudinally to produce a retardation film 5 (λ / 4 plate) with a thickness of 33 μm. The retardation film 5 thus obtained had a refractive index of nx>ny=nz. In addition, the Re(450) / Re(550) of the retardation layer was 1.004, and showed approximately flat dispersion wavelength characteristics. The surface smoothness of the film was 0.32 arcmin.

[0109] [Production Example 1-6: Preparation of Retardation Film 6] A long norbornene resin film (manufactured by Zeon Corporation, product name Zeonor, thickness 50 μm) was stretched at a stretching ratio and stretching temperature so that the in-plane retardation Re (590) was 270 nm, and a retardation film 6 (λ / 2 plate) with a thickness of 33 μm was produced by longitudinally stretching the free end. The retardation film 6 thus obtained had a refractive index of nx>ny=nz. In addition, the Re(450) / Re(550) of the retardation layer was 1.004, and showed approximately flat dispersion wavelength characteristics. The surface smoothness of the film was 0.42 arcmin.

[0110] [Production Example 1-7: Preparation of Retardation Layer (Liquid Crystal Compound Alignment Layer) 7] A liquid crystal composition (coating liquid) was prepared by dissolving 10 g of a polymerizable liquid crystal exhibiting a nematic liquid crystal phase (manufactured by BASF: product name "Paliocolor LC242") and 3 g of a photopolymerization initiator for the polymerizable liquid crystal compound (manufactured by BASF: product name "Irgacure 907") in 40 g of toluene. The surface of a polyethylene terephthalate (PET) film (thickness: 38 μm) was rubbed with a rubbing cloth to perform an alignment treatment. The liquid crystal coating solution was applied to this alignment-treated surface using a bar coater, and the liquid crystal compound was aligned by drying by heating at 90° C. for 2 minutes. The liquid crystal layer thus formed is irradiated with 1 mJ / cm using a metal halide lamp. 2 The liquid crystal layer was cured by irradiating the liquid crystal with light of 1000 nm to form a retardation layer, which was a liquid crystal alignment solidified layer, on the PET film. The retardation layer had a thickness of 1.5 μm and an in-plane retardation Re(590) of 140 nm. Furthermore, the retardation layer exhibited a refractive index characteristic of nx>ny=nz. The retardation layer also exhibited a Re(450) / Re(550) of 1.089, and a positive dispersion wavelength characteristic. This retardation layer can function as a λ / 4 plate. The surface smoothness of the film was 0.18 arcmin.

[0111] [Production Example 1-8: Preparation of Retardation Layer (Liquid Crystal Compound Alignment Layer) 8] A retardation layer having an in-plane retardation Re(590) of 270 nm was obtained in the same manner as in Manufacturing Example 1-7, except that the thickness of the retardation layer was 2.5 μm. The retardation layer exhibited a refractive index characteristic of nx>ny=nz. In addition, the retardation layer had a Re(450) / Re(550) of 1.089, and exhibited a positive dispersion wavelength characteristic. This retardation layer can function as a λ / 2 plate.

[0112] [Manufacturing Example 1-9: Preparation of Retardation Film (Positive C Plate) 9] An autoclave equipped with a stirrer, a cooling tube, a nitrogen inlet tube, and a thermometer was charged with 48 parts by weight of hydroxypropyl methylcellulose (manufactured by Shin-Etsu Chemical, product name: Metolose 60SH-50), 15,601 parts by weight of distilled water, 8,161 parts by weight of diisopropyl fumarate, 240 parts by weight of 3-ethyl-3-oxetanylmethyl acrylate, and 45 parts by weight of t-butyl peroxypivalate as a polymerization initiator, and after nitrogen bubbling was performed for 1 hour, the mixture was maintained at 49°C for 24 hours with stirring to carry out radical suspension polymerization. The mixture was then cooled to room temperature, and the suspension containing the resulting polymer particles was centrifuged. The resulting polymer was washed twice with distilled water and twice with methanol, and then dried under reduced pressure. The resulting fumaric acid ester resin was dissolved in a toluene-methyl ethyl ketone mixed solution (toluene / methyl ethyl ketone 50% by weight / 50% by weight) to prepare a 20% solution. Further, 5 parts by weight of tributyl trimellitate as a plasticizer was added to 100 parts by weight of the fumaric acid ester resin to prepare a dope. A biaxially stretched polyester (polyethylene terephthalate / isophthalate copolymer) film (thickness: 75 μm) was used as the support film. The prepared dope was applied to the support film so that the film thickness after drying was 20 μm, and then dried at 140° C. The coating film (positive C plate) after drying had Re(590)≒0 nm and Rth(590)=-83 nm. The retardation layer had Rth(450) / Rth(550) of 1.012, which indicated positive dispersion wavelength characteristics.

[0113] [Production Example 2: Preparation of polarizing film] As a thermoplastic resin substrate, a long amorphous isophthalic copolymerized polyethylene terephthalate film (thickness: 100 μm) having a Tg of about 75° C. was used, and one side of the resin substrate was subjected to a corona treatment. A PVA aqueous solution (coating liquid) was prepared by adding 13 parts by weight of potassium iodide to 100 parts by weight of a PVA-based resin made by mixing polyvinyl alcohol (polymerization degree 4200, saponification degree 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Mitsubishi Chemical Corporation, product name "GOHSENEX Z410") in a ratio of 9:1, and dissolving the mixture in water. The above PVA aqueous solution was applied to the corona-treated surface of a resin substrate and dried at 60° C. to form a PVA-based resin layer with a thickness of 13 μm, thereby producing a laminate. The obtained laminate was uniaxially stretched 2.4 times in the machine direction (longitudinal direction) in an oven at 130° C. (auxiliary air stretching treatment). Next, the laminate was immersed in an insolubilizing bath (a boric acid aqueous solution obtained by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (insolubilizing treatment). Next, the film was immersed in a dye bath (an aqueous iodine solution obtained by mixing iodine and potassium iodide in a weight ratio of 1:7 with 100 parts by weight of water) at a liquid temperature of 30°C for 60 seconds while adjusting the concentration so that the single transmittance (Ts) of the finally obtained absorptive polarizing film would be the desired value (dyeing process). Next, the piece was immersed in a crosslinking bath (a boric acid aqueous solution obtained by mixing 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with respect to 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (crosslinking treatment). Thereafter, the laminate was immersed in an aqueous boric acid solution (boric acid concentration: 4% by weight, potassium iodide concentration: 5% by weight) at a liquid temperature of 70°C and uniaxially stretched in the longitudinal direction (longitudinal direction) between rolls with different peripheral speeds to a total stretch ratio of 5.5 times (underwater stretching treatment). Thereafter, the laminate was immersed in a cleaning bath (an aqueous solution obtained by mixing 4 parts by weight of potassium iodide with 100 parts by weight of water) at a liquid temperature of 20° C. (cleaning treatment). Thereafter, while drying in an oven maintained at about 90° C., it was brought into contact with a SUS heated roll whose surface temperature was maintained at about 75° C. (drying shrinkage treatment). The shrinkage rate of the laminate in the width direction due to the drying shrinkage treatment was 5.2%. In this manner, an absorptive polarizing film having a thickness of about 5 μm was formed on the resin substrate. A cycloolefin resin film (thickness: 25 μm) was attached as a protective layer to the surface of the obtained absorptive polarizing film (the surface opposite to the resin substrate) via an ultraviolet-curable adhesive. Specifically, the curable adhesive was applied so that the total thickness was about 1 μm, and the layers were attached using a rolling machine. Thereafter, the adhesive was cured by irradiating it with UV light from the cycloolefin resin film side. Then, the resin substrate was peeled off. This resulted in a polarizing film having a cycloolefin resin film / absorption-type polarizing film structure. The polarizing film had a single transmittance (Ts) of 43.4% and a polarization degree of 99.993%.

[0114] [Example 1] The polarizing film obtained in Production Example 2, a retardation film 2 (λ / 2 plate), and a retardation film 1 (λ / 4 plate) were laminated in this order to obtain an optical laminate. Adjacent films were laminated with an acrylic adhesive layer (manufactured by Nitto Denko Corporation, thickness 5 μm) in between. In the laminated film, the relationship between the slow axis of each retardation film and the absorption axis of the polarizing film was such that, when the absorption axis direction of the polarizing film as viewed from the retardation film 1 (λ / 4 plate) was taken as the reference (0°), the angle of the slow axis direction of the retardation film 2 (λ / 2 plate) was 15°, and the angle of the slow axis direction of the retardation film 1 (λ / 4 plate) was 75°.

[0115] [Example 2] The polarizing film obtained in Production Example 2, a retardation layer 4 (λ / 2 plate), and a retardation layer 3 (λ / 4 plate) were laminated together to obtain an optical laminate. Adjacent elements were laminated via an acrylic adhesive layer (manufactured by Nitto Denko Corporation, thickness 5 μm). In the laminated structure, the relationship between the slow axis of each retardation film and the absorption axis of the polarizing film was such that, when the absorption axis direction of the polarizing film as viewed from the retardation layer 3 (λ / 4 plate) was taken as the reference (0°), the angle of the slow axis direction of the retardation layer 4 (λ / 2 plate) was 15°, and the angle of the slow axis direction of the retardation layer 3 (λ / 4 plate) was 75°.

[0116] [Example 3] The polarizing film obtained in Production Example 2, a retardation film 2 (λ / 2 plate), a retardation film 1 (λ / 4 plate), and a retardation film 9 were laminated together to obtain an optical laminate. Adjacent elements were superposed via an acrylic adhesive layer (manufactured by Nitto Denko Corporation, thickness 5 μm). In the superposition, the relationship between the slow axis of each retardation film and the absorption axis of the polarizing film was such that, when the absorption axis direction of the polarizing film as viewed from the retardation film 1 (λ / 4 plate) was taken as the reference (0°), the angle of the slow axis direction of the retardation film 2 (λ / 2 plate) was 15°, and the angle of the slow axis direction of the retardation film 1 (λ / 4 plate) was 75°.

[0117] [Example 4] The polarizing film obtained in Production Example 2, a retardation layer 4 (λ / 2 plate), a retardation layer 3 (λ / 4 plate), and a retardation film 9 were laminated together to obtain an optical laminate. Adjacent elements were laminated via an acrylic adhesive layer (manufactured by Nitto Denko Corporation, thickness 5 μm). In the laminated structure, the relationship between the slow axis of each retardation layer and the absorption axis of the polarizing film was such that, when the absorption axis direction of the polarizing film as viewed from the retardation layer 3 (λ / 4 plate) was taken as the reference (0°), the angle of the slow axis direction of the retardation layer 4 (λ / 2 plate) was 15°, and the angle of the slow axis direction of the retardation layer 3 (λ / 4 plate) was 75°.

[0118] [Experimental Example 1] The polarizing film obtained in Production Example 2, a retardation film 6 (λ / 2 plate), and a retardation film 5 (λ / 4 plate) were laminated together to obtain an optical laminate. Adjacent films were laminated via an acrylic adhesive layer (manufactured by Nitto Denko Corporation, thickness 5 μm). In the laminated film, the relationship between the slow axis of each retardation film and the absorption axis of the polarizing film was such that, when the absorption axis direction of the polarizing film as viewed from the retardation film 5 (λ / 4 plate) was taken as the reference (0°), the angle of the slow axis direction of the retardation film 6 (λ / 2 plate) was 15°, and the angle of the slow axis direction of the retardation film 5 (λ / 4 plate) was 75°.

[0119] [Experimental Example 2] The polarizing film obtained in Production Example 2, a retardation film 6 (λ / 2 plate), a retardation film 5 (λ / 4 plate), and a retardation film 9 were laminated together to obtain an optical laminate. Adjacent films were laminated via an acrylic adhesive layer (manufactured by Nitto Denko Corporation, thickness 5 μm). In the laminated film, the relationship between the slow axis of each retardation film and the absorption axis of the polarizing film was such that, when the absorption axis direction of the polarizing film as viewed from the retardation film 5 (λ / 4 plate) was taken as the reference (0°), the angle of the slow axis direction of the retardation film 6 (λ / 2 plate) was 15°, and the angle of the slow axis direction of the retardation film 5 (λ / 4 plate) was 75°.

[0120] [Experimental Example 3] The polarizing film obtained in Production Example 2, a retardation layer 8 (λ / 2 plate), and a retardation layer 7 (λ / 4 plate) were laminated together to obtain an optical laminate. Adjacent elements were laminated via an acrylic adhesive layer (manufactured by Nitto Denko Corporation, thickness 5 μm). In the laminated structure, the relationship between the slow axis of each retardation film and the absorption axis of the polarizing film was such that, when the absorption axis direction of the polarizing film as viewed from the retardation layer 7 (λ / 4 plate) was taken as the reference (0°), the angle of the slow axis direction of the retardation layer 8 (λ / 2 plate) was 15°, and the angle of the slow axis direction of the retardation layer 7 (λ / 4 plate) was 75°.

[0121] [Experimental Example 4] The polarizing film obtained in Production Example 2, a retardation layer 8 (λ / 2 plate), a retardation layer 7 (λ / 4 plate), and a retardation film 9 were laminated together to obtain an optical laminate. Adjacent elements were laminated via an acrylic adhesive layer (manufactured by Nitto Denko Corporation, thickness 5 μm). In the laminated structure, the relationship between the slow axis of each retardation film and the absorption axis of the polarizing film was such that, when the absorption axis direction of the polarizing film as viewed from the retardation layer 7 (λ / 4 plate) was taken as the reference (0°), the angle of the slow axis direction of the retardation layer 8 (λ / 2 plate) was 15°, and the angle of the slow axis direction of the retardation layer 7 (λ / 4 plate) was 75°.

[0122] <Evaluation> The following evaluations were carried out for each example. 1. Ellipticity Using a Mueller matrix polarimeter (manufactured by Axometrics, product name "Axoscan"), light of a specified wavelength (450 nm, 550 nm, 650 nm) was incident on the polarizing member side of the optical laminate at 23°C, and the ellipticity of the light exiting the phase difference member was measured. The incident angle and the exit angle were set to a polar angle of 30°, and the ellipticity was measured at azimuth angles of 11.25° each in the range of azimuth angles from 0° to 360°. The minimum and average values ​​of the 32 measured values, as well as the number of data points that are 0.85 or greater, are shown in Table 1. The ellipticity was also measured with the incident angle and the exit angle set as a polar angle of 0. The measured values ​​are shown in Table 1.

[0123] [Table 1]

[0124] 2. Depolarization Using a Mueller matrix polarimeter (Axometrics, product name "Axoscan"), light of a specified wavelength (450 nm, 550 nm, 650 nm) was incident on the polarizing member side of the optical laminate at 23°C. From the obtained Mueller matrix, the depolarization index (DI) was calculated using the following formula, and the depolarization property was evaluated by subtracting the depolarization index (DI) from 1 (1-DI).

number

[0125] [Table 2] [Industrial Applicability]

[0126] A display system according to an embodiment of the present invention can be used in a display device such as VR goggles. [Explanation of symbols]

[0127] 2. Display System 10 Polarizing member 12 Display element 14 Reflector 16 First lens section 18 Half Mirror 20 First phase difference member 22 Second phase difference member 24 Second lens section 200 Optical laminate

Claims

1. 1. A display system for displaying an image to a user, comprising: a display element having a display surface that emits light representing an image forward via a polarizing member; a reflecting section disposed in front of the display element, the reflecting section including a reflective polarizing member and configured to reflect light emitted from the display element; a first lens portion disposed on an optical path between the display element and the reflector; a half mirror disposed between the display element and the first lens portion, the half mirror transmitting light emitted from the display element and reflecting the light reflected by the reflecting portion toward the reflecting portion; a first phase difference member disposed on an optical path between the display element and the half mirror; a second phase difference member disposed on an optical path between the half mirror and the reflecting portion, the polarizing member and the first phase difference member constitute an optical laminate, The optical laminate includes a polarizing member, a layer functioning as a λ / 2 plate, and a layer functioning as a λ / 4 plate, in this order. Display system.

2. 2. An optical laminate for use in the display system according to claim 1, comprising a polarizing member, a layer functioning as a λ / 2 plate, and a layer functioning as a λ / 4 plate, in that order.

3. 3. The optical laminate according to claim 2, wherein the layer functioning as a λ / 2 plate has an in-plane retardation Re(550) of 230 nm to 330 nm.

4. 3. The optical laminate according to claim 2, wherein the layer functioning as a λ / 4 plate has an in-plane retardation Re(550) of 100 nm to 200 nm.

5. 3. The optical laminate according to claim 2, wherein the angle between the slow axis of the layer functioning as a λ / 2 plate and the absorption axis of the polarizing member is 5° to 35°.

6. 3. The optical laminate according to claim 2, wherein the angle between the slow axis of the layer functioning as a λ / 4 plate and the absorption axis of the polarizing member is 55° to 85°.

7. The optical laminate according to claim 2 , wherein the layer functioning as a λ / 2 plate exhibits inverse dispersion wavelength characteristics.

8. The optical laminate according to claim 2 , wherein the layer functioning as a λ / 4 plate exhibits reverse dispersion wavelength characteristics.

9. Further comprising a member having a refractive index characteristic that satisfies the relationship of nz>nx=ny, the member having the refractive index characteristic showing the relationship of nz>nx=ny is disposed on the side of the layer functioning as the λ / 4 plate opposite to the layer functioning as the λ / 2 plate; The optical laminate according to claim 2 .

10. Further comprising an anti-reflection protective member, The anti-reflection protective member is disposed on the outermost side opposite to the polarizing member. The optical laminate according to claim 2 .

11. 3. The optical laminate according to claim 2, wherein the depolarization index (DI) of transmitted light having a wavelength of 550 nm measured at a polar angle of 0° is subtracted from 1 (1-DI) to obtain a value of 99.5% or more.

12. The optical laminate according to claim 2, wherein the depolarization index (DI) of transmitted light having a wavelength of 550 nm measured at a polar angle of 30° and an azimuth angle of 0° to 360° is subtracted from 1 (1-DI) to be 99.4% or more.

13. A step of passing light representing an image outputted through a polarizing member through a first phase difference member; A step of causing the light having passed through the first phase difference member to pass through a half mirror and a first lens portion; A step of passing the light that has passed through the half mirror and the first lens portion through the second phase difference member; A step of reflecting the light that has passed through the second phase difference member toward the half mirror by a reflective polarizing member; a step of allowing the light reflected by the reflective polarizing member and the half mirror to pass through the reflective polarizing member by the second phase difference member; The display method includes the first phase difference member. The optical laminate according to claim 2 .

Citation Information

Patent Citations

  • Laminate for organic el displays and circular polarizing plate used therefor

    JP2021103286A